1996
DOI: 10.1073/pnas.93.4.1585
|View full text |Cite
|
Sign up to set email alerts
|

Cationic facial amphiphiles: a promising class of transfection agents.

Abstract: A promising class of compounds for DNA transfection have been designed by conjugating various potyamines to bile-acid-based amphiphiles. Formulations containing these compounds were tested for their ability to facilitate the uptake of a 3-galactosidase reporter plasmid into COS-7 cells. Dioleoyl phosphatidyl ethanolamine (DOPE) formulations of some of the compounds were several times better than Lipofectin at promoting DNA uptake. The most active compounds contained the most hydrophilic bile acid components.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 31 publications
2
75
0
Order By: Relevance
“…The positive charge sets 9 apart from the taurine conjugates and other negatively charged bile salts, and suggests that it is worth investigating whether positively charged groups are useful features to include in the design of other absorption promoters. Cationic lipids and other cationic polymers have been shown to increase the uptake of plasmid DNA and other negatively charged oligonucleotides in various cell types (22)(23)(24)(25)(26)(27)(28). The efficacy of cationic polymers in DNA delivery has been partly attributed to their attraction for negatively charged cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The positive charge sets 9 apart from the taurine conjugates and other negatively charged bile salts, and suggests that it is worth investigating whether positively charged groups are useful features to include in the design of other absorption promoters. Cationic lipids and other cationic polymers have been shown to increase the uptake of plasmid DNA and other negatively charged oligonucleotides in various cell types (22)(23)(24)(25)(26)(27)(28). The efficacy of cationic polymers in DNA delivery has been partly attributed to their attraction for negatively charged cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…In a seminal work, Kahne and co-workers [11] designed a new family of compounds based on the idea that facially amphiphilic components known to destabilize membranes might increase the fusiogenic potential of the transfecting particles and thereby enhance DNA uptake. After observing some abstract similarities between certain amphiphilic peptides that promote DNA uptake [12] and polyhydroxylated steroids, they designed several amphiphilic bile acid derivatives (e.g.…”
Section: The Facial Amphiphilicity Conceptmentioning
confidence: 99%
“…Kahne et al ¢rst reported facial amphiphiles derived from cholic acid prepared for use as transfection agents [21]. These compounds, prepared from cholic acid with carbohydrates appended on one face of the molecule (1 in Fig.…”
Section: Membrane-active Antibioticsmentioning
confidence: 99%